Analisis Prioritas Konsep Dan Strategi Penanganan Kawasan Permukiman Kumuh Di Kecamatan Nambo - Astija, Sitti; Kadir, Ishak; Yusuf, Dewi Nurhayati (Jurnal Perencanaan Wilayah, 2021)
ABSTRACTThe slum areas at Nambo sub-district are divided into Pudai - Nambo Cluster (Bungkutoko, Petoaha, Nambo Kelurahan) and the Tondonggeu - Sambuli Cluster. The typologies of settlements in Nambo sub-district are lowlands and water banks. This study aims to analyze the priority scale, to determine the concepts and strategies for slum areas improvement in Nambo sub-district. The method used in this research is quantitative descriptive by assigning a weighting analysis of slum area priority indicators based on Ministry of Public Works and Public Housing Regulation No.2 / 2016. The results show that the slum area in Nambo sub-district is divided into two priority classifications, namely moderate slum, illegal land status and other considerations of high and moderate slum, illegal land status and other moderate considerations. Based on the slum conditions in Nambo District, the concept / treatment pattern of slum area is towards resettlement, with formulation strategies; land preparation, rehabilitation / improvement of residential buildings, rehabilitation / improvement and rehabilitation of settlement infrastructure / improvement of fire protection.Keywords: Slum Area, Concept,  Nambo, Priority, StrategyABSTRAK Kawasan permukiman kumuh di Kecamatan Nambo terbagi atas Kluster Pudai – Nambo (Kelurahan Bungkutoko, Petoaha, Nambo) dan Kluster Tondonggeu – Sambuli. Tipologi permukiman di Kecamatan Nambo merupakan dataran rendah dan tepi air. Penelitian ini bertujuan untuk menganalisis skala prioritas, menentukan konsep dan strategi penanganan kawasan kumuh di Kecamatan Nambo. Metode yang digunakan dalam penelitian ini yaitu deskriptif kuantitatif dengan menggunakan analisis pembobotan indikator prioritas kawasan kumuh berdasarkan Peraturan Menteri PU No. 2 Tahun 2016. Hasil penelitian menunjukkan bahwa kawasan kumuh di Kecamatan Nambo terbagi atas dua klasifikasi prioritas yaitu kumuh sedang, status lahan tidak legal dan pertimbangan lainnya tinggi dan kumuh sedang, status lahan tidak legal dan pertimbangan lain sedang. Berdasarkan kondisi kekumuhan di Kecamatan Nambo maka konsep/ pola penanganan kawasan permukiman kumuh yaitu permukiman kembali. Rumusan strategi; penyiapan lahan, rehabilitasi/perbaikan bangunan hunian, rehabilitasi/ perbaikan infrastruktur permukiman dan rehabilitasi/ perbaikan proteksi kebakaran.Kata Kunci : Kawasan Kumuh, Konsep, Nambo, Prioritas, Strategi